The potential benefits of route guidance - Jeffery, D. J. (Transport and Road Research Laboratory, 1981)
Route choices made by drivers in a sample in Gloucestershire are analysed to show the proportion of driver journey costs which are unnecessarily incurred by drivers who fail to select optimum routes.